Identifikasi dan Analisis Beban Kerja Mental Karyawan menggunakan Metode NASA TLX di PT XYZ - Tigor Gabriel Pasaribu; Asep Erik Nugraha (Jurnal Serambi Engineering, 2023)
PT XYZ is one of the companies in Indonesia engaged in providing telecommunications products. There are several interconnected and systematic teams at PT XYZ including the OBL, SM/PRPO, Solution and Reporting Data teams which are related to human resources and have jobs that create their own workload in order to achieve the tasks that have been done. PT XYZ wants to know the value of the large mental workload that the workforce gets on its four teams by applying the NASA TLX method. The aim of this research is to be able to identify events and investigate the risks of mental workload, rating levels and suggestions for improving work systems for employees of the OBL, SM/PRPO, Solution and Reporting Data teams at PT XYZ. Based on the mental workload score using the NASA-TLX method, it was found that 14 employees had a very high mental work load, while 2 employees had a high mental work load. Then, for the most dominant variable, it can affect the final mental work load according to the questionnaire that was given before, namely effort and performance. Proposals for improvements that can be shared in order to reduce the score/rating of employees' mental workload, namely by adding employees according to the needs of the relevant team members and also the company, training activities on anticipating mental workload and sharing sessions among fellow employees regarding hearings about complaints annoyed while working.